Budget Deficits and Budget Institutions - Alesina, Alberto (IMF Working Papers; Working Paper ;, 1996)
By discussing the available theoretical and empirical literature, this paper argues that budget procedures and budget institutions do influence budget outcomes. Budget institutions include both procedural rules and balanced budget laws. We critically assess theoretical contributions in this area and suggest several open and unresolved issue. We also examine the empirical evidence drawn from studies on samples of OECD countries, Latin American countries and the United States. We conclude with a discussion of the normative implications of this literature and with some concrete proposals.